2008
DOI: 10.1180/minmag.2008.072.1.385
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption studies of Mo and Vonto ferrihydrite

Abstract: In this paper, the kinetics of Mo and V (100 mM) uptake on ferrihydrite (FHY) were evaluated in batch, mono-sorbate systems at pH between 4 and 9, and in bi-sorbate systems in the presence of P (100 mM) at pH 7. In the Mo and V single-sorbate experiments, 100% adsorption was observed at pH values below 6 and 8, respectively. Above the point of zero charge (PZC = 7.97) of FHY, the adsorption efficiency for Mo dropped dramatically (20% at pH 8) while V showed high uptake efficiencies even at pH 9 (60% efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 12 publications
0
33
2
Order By: Relevance
“…Competition with other ions also impacts sorption. Vanadate competes with other oxyanions such as phosphate, arsenate, selenate and molybdate for sites on positively charged mineral surfaces (Blackmore et al, 1996;Brinza et al, 2008;Wang et al, 2003). Prathap and Namasivayam (2010) proposed an order of adsorption among common oxyanions and chloride to positively charged metal oxide surfaces of: vanadate > phosphate > selenate > molybdate; sulfate, nitrate and chloride showed no effect on V(V) adsorption.…”
Section: Adsorption To Metal Oxide Mineralsmentioning
confidence: 94%
“…Competition with other ions also impacts sorption. Vanadate competes with other oxyanions such as phosphate, arsenate, selenate and molybdate for sites on positively charged mineral surfaces (Blackmore et al, 1996;Brinza et al, 2008;Wang et al, 2003). Prathap and Namasivayam (2010) proposed an order of adsorption among common oxyanions and chloride to positively charged metal oxide surfaces of: vanadate > phosphate > selenate > molybdate; sulfate, nitrate and chloride showed no effect on V(V) adsorption.…”
Section: Adsorption To Metal Oxide Mineralsmentioning
confidence: 94%
“…[4] Further, ferric oxyhydroxide has shown to be important for adsorption of dissolved vanadium in waters. [5][6][7][8] Studies made on soils have shown a similar pattern where the oxide concentration in the soil plays an important role for vanadium retention. [9][10] The adsorption to metal (hydr)oxides is strongly dependent on the type of (hydr)oxide as well as on solution pH and on the solid:solution ratio.…”
Section: Introductionmentioning
confidence: 93%
“…For Sb this could partly be attributed to the decreased adsorption at high pH, discussed previously. Brinza et al [13] reported decreased Mo adsorption even at pH 7. Gustavsson [12] observed that little molybdate adsorption occurred at pH values above 9 under given experimental conditions and that tungstate adsorbed stronger than molybdate to FH, which is in accordance with our results.…”
Section: Diffusion Coefficient Measurementsmentioning
confidence: 98%
“…In oxygenated waters arsenic, antimony, molybdenum, vanadium and tungsten are predicted to be present in their anionic forms; arsenate, As(V), antimonate, Sb(V), molybdate, Mo(VI), vanadate, V(V) and tungstate, W(VI) [11], all showing tendencies to adsorb to ferric oxides (e.g. As: [5]; Mo, W: [12]; V, Mo: [13]; Sb: [14]). …”
Section: Introductionmentioning
confidence: 99%